Predicting stock price and spread movements from news - Wistbacka Pontus; Rönnqvist Samuel; Vozian Katia; Sagade Satchit (United States, 2022)
We explore several ways of using news articles and financial data to train neural network machine learning models to predict shock events in high-frequency market data, and aggregated shock episodes. We investigate the use of price movements in this context, and separately at a daily interval as well. We describe in detail how training sets are created from our data sources and how our machine learning models are trained. We find that pairing company-related news text with events or movements in financial time series proves less straight-forward than the literature would indicate. We discuss possible reasons for negative results, especially relating to the combination of minute-level news and millisecond-level market data.
Proceedings of the 54th Annual Hawaii International Conference on System Sciences